Assessment of visual, auditory, and kinesthetic learning style among undergraduate nursing students - Hussein Ibrahim, Radhwan; Hussein, Dhiaa Al-rahman (International Journal of Advanced Nursing Studies, 2015)
Background: Learning styles refer to the ability of learner to perceive and process information in learning situations. The ability to understand students’ learning styles can increase the educational outcomes. VAK (Visual, auditory, kinesthetic) learning style is one of the learning style in which students use three of sensory perception to receive information. Teachers can incorporate these learning styles in their classroom activities so that students are competent to be successful in their courses. The purpose of this study is to assess Visual, Auditory, and Kinesthetic learning style among undergraduate nursing students.Methods: A descriptive study was carried out; the study was conducted during the period of 3rd. November, 2013-15, March, 2014, in two Nursing Colleges at Universities of Mosul and Kirkuk. A stratified random sampling was used for data collection. The target population was an undergraduate nursing students (210) students (60 male and 150 female). Statistical Package for the Social Science (SPSS), Chi-square, Frequencies and Percentage was used for data analysis.The results: the findings reveal that Visual, Auditory, and Kinesthetic learning style of the study sample was (40.0%), (29.5%), and 30.5% respectively. Females preferred auditory learning style (30.3%) more than males (27.3%), while males preferred kinesthetic learning style (32.3%) more than females (29.8%).Recommendation: The researcher recommended that nurse educators should aware of learning styles of the students and provide teaching style to be matched with their learning style.